2021
DOI: 10.3390/medsci9010009
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular Filtration Secretion Driven by Mechanical Force Contributes to Small Intestinal Fluid Dynamics

Abstract: Studies of fluid secretion by the small intestine are dominated by the coupling with ATP-dependent generation of ion gradients, whereas the contribution of filtration secretion has been overlooked, possibly by the lack of a known mechanistic basis. We measured apical fluid flow and generation of hydrostatic pressure gradients by epithelia of cultured mouse enterocytes, Caco-2 and T-84 cells, and fibroblasts exposed to mechanical force provided by vigorous aeration and in response to ion gradients, inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Organoid swelling was partly attenuated with the Na(+)-K(+)-Cl(−) cotransporter (NKCC1) inhibitor bumetanide, demonstrating Cl − dependence of forskolin-induced organoid fluid secretion ( Fig S2E and F ). Lack of complete inhibition may be explained by reabsorption and recycling of luminal-secreted Cl − or an ion channel–independent mechanism underlying fluid secretion caused by mechanical forces ( Bajko et al, 2020 ; Buddington et al, 2021 ). Moreover, chemical CFTR inhibitors significantly reduced FIS in HC NAOs ( Fig S2G and H ), indicating CFTR dependence.…”
Section: Resultsmentioning
confidence: 99%
“…Organoid swelling was partly attenuated with the Na(+)-K(+)-Cl(−) cotransporter (NKCC1) inhibitor bumetanide, demonstrating Cl − dependence of forskolin-induced organoid fluid secretion ( Fig S2E and F ). Lack of complete inhibition may be explained by reabsorption and recycling of luminal-secreted Cl − or an ion channel–independent mechanism underlying fluid secretion caused by mechanical forces ( Bajko et al, 2020 ; Buddington et al, 2021 ). Moreover, chemical CFTR inhibitors significantly reduced FIS in HC NAOs ( Fig S2G and H ), indicating CFTR dependence.…”
Section: Resultsmentioning
confidence: 99%
“…Shao et al [ 297 ] also observed a zinc-induced increase in TER across Caco-2 cell layers while also seeing increased ZO-1 expression, changes they observed were being transduced by the PI3K/AKT pathway. Furthermore, in Caco-2 cell layers, zinc was found to reduce the bulk transepithelial fluid flow, including lower transepithelial diffusion of FITC-dextran (4 kDa) [ 298 ]. A somewhat related study in Caco-2 showed that downregulating the ZnR/GPR39 zinc-sensing receptor decreased TER and reduced the expression of occludin and ZO-1 [ 299 ].…”
Section: Can Elevated Micronutrient Levels (Supplementation) Improve ...mentioning
confidence: 99%
“…6 Chloride secretion and related water transport are considered the leading causes of secretory diarrhea and this phenomenon is well known and described in other studies. 3,[7][8][9] Increased chloride secretion is accompanied by a decrease in sodium ion absorption; however, these processes are much less understood. Chloride secretion is aggravated by serotonin (5-hydroxytryptamine (5-HT)).…”
Section: Introductionmentioning
confidence: 99%